3D Echocardiography for Rheumatic Heart Disease Analysis: Ready for Prime Time - Vieira, Marcelo Luiz Campos; Branco, Carlos Eduardo de Barros; Gazola, Alessandra Santos Lima; Vieira, Paulo Pinto Alves Campos; Benvenuti, Luiz Alberto; Demarchi, Léa Maria Macruz Ferreira; Gutierrez, Paulo Sampaio; Aiello, Vera Demarchi; Tarasoutchi, Flávio; Sampaio, Roney Orismar (Frontiers in Cardiovascular Medicine, 2021)
Rheumatic heart disease (RHD) remains to be a very important health issue worldwide, mainly in underdeveloped countries. It continues to be a leading cause of morbidity and mortality throughout developing countries. RHD is a delayed non-suppurative immunologically mediated inflammatory response to the throat infection caused by a hemolytic streptococcus from the A group (Streptococcus pyogenes). RHD keeps position 1 as the most common cardiovascular disease in young people aged <25 years considering all the continents. The disease can lead to valvular cardiac lesions as well as to carditis. Rheumatic fever valvular injuries lead most commonly to the fusion and thickening of the edges of the cusps and to the fusion, thickening, and shortening of the chordae and ultimately to calcification of the valves. Valvular commissures can also be deeply compromised, leading to severe stenosis. Atrial and ventricular remodeling is also common following rheumatic infection. Mixed valvular lesions are more common than isolated valvular disorders. Echocardiography is the most relevant imaging technique not only to provide diagnostic information but also to enable prognostic data. Further, it presents a very important role for the correction of complications after surgical repair of rheumatic heart valvulopathies. Three-dimensional (3D) echocardiography provides additional anatomical and morphofunctional information of utmost importance for patients presenting rheumatic valvopathies. Accordingly, three-dimensional echocardiography is ready for routine use in patients with RHD presenting with valvular abnormalities.